Differential elimination of marked sex chromosomes enables production of nontransgenic male mosquitoes in a single strain - Austin Compton; Atashi Sharma; Melanie Hempel; Azadeh Aryan; James K. Biedler; Mark B. Potters; Karthikeyan Chandrasegaran; Clément Vinauger; Zhijian Tu (Proceedings of the National Academy of Sciences, 2025)
Diverse genetic strategies are being pursued to control mosquito-borne infectious diseases. These strategies often rely on the release of nonbiting males to either reduce the target mosquito population or render them resistant to pathogens. Male-only releases are important as any contaminating females can bite and potentially transmit pathogens. Despite significant efforts, it remains a major bottleneck to reliably and efficiently separate males from females, especially when nontransgenic males are preferred. In the yellow fever mosquito Aedes aegypti , sex is determined by a pair of homomorphic sex chromosomes, with the dominant male-determining locus (the M locus) and its counterpart (the m locus) embedded in an M-bearing and an m-bearing chromosome 1, respectively. We utilized both naturally occurring and engineered sex-linked recessive lethal alleles (RLAs) to create sex separation strains for Ae. aegypti on the basis of differential elimination of marked sex chromosomes (DeMark). DeMark strains are self-sustaining and produce nontransgenic males that are readily separated from individuals carrying RLA- and transgene-marked m chromosomes. For example, the marked m chromosome in the heterozygous mother in some strains was only inherited by her female progeny due to RLA-mediated incompatibility with the M-bearing chromosome in the father, producing nontransgenic males and transgenic females, generation after generation. We further explore strategies to conditionally eliminate females that contain marked sex chromosomes. We also discuss DeMark designs that are applicable for efficient sex separation in organisms with well-differentiated X and Y chromosomes, such as the Anopheles mosquitoes.